Cognitive Bias Modification for Interpretation in Major Depression: Effects on Memory and Stress Reactivity - Joormann, Jutta (Clin Psychol Sci, 2015)
Interpreting ambiguous stimuli in a negative manner is a core bias associated with depression. Investigators have used cognitive bias modification for interpretation (CBM-I) to demonstrate that it is possible to experimentally induce and modify these biases. This study extends previous research by examining whether CBM-I affects not only interpretation, but also memory and physiological stress response in individuals diagnosed with Major Depressive Disorder (MDD). We found that CBM-I was effective in inducing an interpretive bias. Participants also exhibited memory biases that corresponded to their training condition and demonstrated differential physiological responding in a stress task. These results suggest that interpretation biases in depression can be modified, and that this training can lead to corresponding changes in memory and to decreases in stress reactivity. Findings from this study highlight the importance of examining the relations among different cognitive biases in MDD and the possibility of modifying cognitive biases.